The Poetical Works of Mrs. Leprohon (Miss R.E. Mullins) - Leprohon, Mrs. (Rosanna Eleanor), 1829-1879 (Book collections on Project MUSE., 1973)
This volume attempts to classify poems in a way which would best show the range of Mrs. Leprohon's power, though in this sketch we have dwelt upon her work as a poet, it is as a writer of fiction that she has won her most marked popular successes, that she has reached the hearts of the two great communities of which this province is composed.